PREDICTORS OF GUILT AND SHAME: RELATIONAL HEALTH, FAMILY EXPERIENCES, AND TRAUMA - Foughty, Deni (My University, 2018)
Tangney and Dearing (2002) found evidence that shame and relational disconnection were significantly related and that shame linked to psychological distress. Relational-cultural theorists, Miller and Stiver (1997) believed chronic disconnection can lead to psychological distress and worse, psychological isolation, what they believe to be the most destructive and terrifying feeling a person can experience. Brown (2007) found shame was the cause and result of relational disconnection. Other experiences, such as trauma history and family experiences, have been linked to shameful emotions (Dorahy et al, 2013; Katz & Nelson, 2007). These links with shame are important to understand because healthy relationships (i.e. empowering, engaging, and authentic) have been demonstrated to increase psychological wellbeing, health, and positive psychosocial outcomes (Frey, Tobin, & Beesley, 2004; Guyll, Cutrona, Burtzette, & Russell, 2010). These findings were supported by this study whose purpose was to determine if there were predictive relationships between relational health, trauma history, family experiences, and guilt and shame proneness. Guilt and shame were found to significantly predict each other. Age and negative family experiences were found to be significant predictors of increased guilt proneness, while trauma history was found to be the most significant predictor of increased shame proneness. Community and peer relational health were found to significantly reduce shame, although only peer relational health was found to increase guilt proneness.
Keywords: Guilt; Shame; Relationships; Family; Trauma